A Multidisciplinary Approach to Managing Multiple Tuberous Xanthomas in a Pediatric Patient with Familial Hypercholesterolemia Type II: A Rare Case - Clarissa Maharani Putri; Rina Gustia; Ennesta Asri; Mutia Sari; Indah Indria Sari (HM Publisher, 2025)
Background: Familial hypercholesterolemia (FH) is a rare inherited disorder characterized by high cholesterol levels, primarily high levels of low-density lipoprotein cholesterol (LDL-C). This condition can lead to premature cardiovascular disease. A less recognized but significant manifestation of FH is the development of multiple tuberous xanthomas, which are exogenous masses or fatty deposits on the skin. Case presentation: This report describes the case of a 4-year-old female child who presented to the Dermatology, Venereology, and Aesthetics Department of Dr. M. Djamil General Hospital Padang with multiple yellowish, painless, and non-itchy lumps on her body. These lumps were located on her knuckles, hands, elbows, buttocks, knees, back of knees, ankles, and feet. The lumps had been progressively increasing in size over the past month. Her medical history revealed that she first developed a yellowish lump on her right ankle two years prior, which gradually spread to other areas of her body. A dermoscopic examination showed a yellow-brown structureless area, and laboratory tests confirmed hypercholesterolemia with elevated LDL levels. Her triglycerides were normal, and both of her parents also had hypercholesterolemia. A histopathology examination confirmed the diagnosis of xanthoma. The patient was diagnosed with tuberous xanthomas and treated with simvastatin 1x10 mg, along with surgical excision of the xanthomas and flap reconstruction under general anesthesia. Conclusion: This case highlights the importance of a multidisciplinary approach in managing multiple tuberous xanthomas in a child with FH. While surgical excision can effectively remove the lesions, ongoing lipid-lowering therapy is crucial to prevent recurrence and reduce cardiovascular risks associated with FH. Collaboration among dermatologists, pediatric cardiologists, and pediatric nutritionists is vital to ensure comprehensive care and enhance the patient's overall quality of life.